Fiscal management in adjustment lending - Datta Mitra, Jayati; World Bank. (Washington, D.C. : World Bank, 1997)
This study analyzes the World Bank's experience with fiscal management in 250 adjustment operations in 86 countries. It examines the fiscal records in a sample of 26 countries grouped by region, portfolio characteristics, and economic traits. The study confirms that fiscal deficit reduction is associated with improved external balances and economic growth and that it takes sustained, long-term effort, and continual vigilance against reversals. Fiscal mismanagement, not exogenous shocks, was the principal cause of persistent budget deficits.
Includes bibliographical references.
aia 18/07/16
Keywords: Fiscal policy; Loans, Foreign; Budget deficits; Structural adjustment (Economic policy)